Analisis Perlengkapan Peralatan Kantor Bagian Akuntansi pada PT Pertamina - Fakhrul Aimar Muttaqin; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The aim of this research is to determine the office equipment at PT Pertamina Kota Central Jakarta which includes the various equipment used and the condition of the equipment. This research uses a qualitative method with a descriptive approach, namely by describing and analyzing the problems found. The subjects of this research are four employees of PT Pertamina Kota Central Jakarta in the accounting, general and service departments. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews and documentation, while secondary data was obtained through books, previous research and articles related to research. From the results of this research, it can be seen that the PT Pertamina City Central Jakarta office has equipped various types of equipment ranging from computers, printers, photocopy machines, telephones, and small equipment such as hvs paper, pens. With all the machine equipment, there are only a few pieces of equipment that are damaged, such as computers and printers, this can have an impact on employee performance. Apart from that, complete office equipment also really supports employee comfort in working, not only employees but also every guest or member of the public who visits will feel comfortable too.